2015
DOI: 10.1590/2317-1782/20152014002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of students from private and public schools on the spelling performance

Abstract: Spelling ability and performance of students from the private and public schools are not similar in the fourth and sixth grades, but it is in the fifth grade. Spelling errors are gradually overcome as education progresses; however, this overcome rate was considerable between the fourth and fifth grades in the public schools. Decrease in the types of spelling errors follows a hierarchy of categories: phoneme/grapheme conversion, simple contextual rules, complex contextual rules, and language irregularities. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…It was also observed that the phonological errors that alter the phoneme were more frequent than the errors that alter the syllabic structure, followed by the contextual-arbitrary and the phonetically motivated ones. Some studies (3,13,25,26) have analyzed errors in writing. One of them (13) described the orthographic performance of children without complaints of language and/or learning difficulties reported by parents and/or teachers and concluded that among the errors found in writing were phonological substitutions followed by omissions and substitutions orthographic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also observed that the phonological errors that alter the phoneme were more frequent than the errors that alter the syllabic structure, followed by the contextual-arbitrary and the phonetically motivated ones. Some studies (3,13,25,26) have analyzed errors in writing. One of them (13) described the orthographic performance of children without complaints of language and/or learning difficulties reported by parents and/or teachers and concluded that among the errors found in writing were phonological substitutions followed by omissions and substitutions orthographic.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the spelling errors are gradually overcome as the schooling and formal teaching of spelling advances. The fact that writing errors become less common as the child progresses in literacy is reported in the literature (3,7,12,25,26) and justified by increased reading exposure (7) . A study (25) verified that the students of the 2nd and 3rd years had similar levels of knowledge of spelling; and this was higher than that of first year students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this perspective, unconventional spelling can be considered part of the acquisition of writing (9) and that its appearance often results from the recovery that children make of speech characteristics (9) . Thus, in a literate society, characteristics of speech and writing would be related, however, indirectly, since writing would be the product of the insertion of the writer in oral social and literate social practices.…”
Section: Introductionmentioning
confidence: 99%